Study of grafting of polylactic acid and its copolymer with 12-hydroxy stearic acid on the surface of MWCNT by 13CCP/MAS and AFM - Pandey, Asutosh K.; Garnaik, Baijayantimala (International Journal of Research in Pharmacy and Chemistry, 2013)
The purpose of this study to study the structure property relationship of grafted material on MWCNT, the determination of NMR nuclei spin-lattice (T1) and spin-spin (T2) relaxation times suggest that the broaden signals are associated with diamagnetic species namely the nanotube attached polymer moieties. the AFM image of PLA oligomer grafted MWCNTs and topography patterns comprised of height from 0-250 nm and the side lengths ranging from 0.0 to 7.7 µm. Surface patches are formed randomly distributed employing that the presence of side chain hanged at 12-postion in the copolymer grafted on MWCNTs.